Freedom of Religion or Belief and Employment Law - Vickers, Lucy (Religion and human rights, 2017)
This article explores the extent to which the jurisprudence of the European Convention on Human Rights has promoted the protection of freedom of religion or belief in the context of the workplace since the decision in Kokkinakis v. Greece. As a preliminary question, it explores whether and why freedom of religion or belief extends to the employment relationship. It then considers two main areas where freedom of religion or belief interacts with employment: the rights of religious workers to manifest religion or belief at work, and the rights of religious organisations to impose religious requirements on their staff.